Analisis Penggunaan Metode Demonstrasi pada Pembelajaran Tematik Integratif pada Kelas V SDN Sekip II Surakarta Tahun Pelajaran 2021/2022 - Erlin Moneta; Sri Handayani; Oktiana Handini (Departement of Mathematics Education, 2023)
The purposes of this study are 1) To find out the application of the Demonstration Method in Integrative Thematic Learning in Class V of SDN SEKIP II Surakarta in the 2021/2022 Academic Year. 2) To find out the impact of using the Demonstration Method on Integrative Thematic Learning in Class V of SDN SEKIP II Surakarta in the 2020/2021 Academic Year. This type of research used is descriptive qualitative. The subjects used in this study were students in class V at SEKIP II Surakarta Public Elementary School for the 2021/2022 academic year. Data collection methods are interviews, questionnaires, and documentation. Structured interviews were used to obtain the required information. The research questionnaire was used to obtain data. Documentation in the form of student data, lesson plans, photos of research activities, and school profiles. The validity of the data uses source triangulation and technical triangulation. Data analysis in this study includes data reduction. Data presentation and verification. Based on the data analysis that has been carried out, the following results are obtained: 1) The use of the demonstration method in integrative thematic learning in class V SEKIP II Surakarta State Elementary School, creates a pleasant atmosphere that is not boring because the demonstration method can help students learn about an event or thing others in learning directly even if only with a replica of an object or an imitation of an event that is being conveyed or explained by the class teacher. 2) The impact of using this demonstration method can accelerate students' understanding of the messages presented in an incident or other things conveyed by the teacher. With this, it can increase focus on learning by students.